3D bioprinting of a perfusable skin-on-chip model suitable for drug testing and wound healing studies - Federico Maggiotto; Eva Dalla Valle; Anna Fietta; Lorenzo Maria Visentin; Monica Giomo; Elisa Cimetta (Materials Today Bio)
The skin, as the body's largest organ, serves critical functions including physical protection, thermoregulation, sensation, and immunity, making it a key focus in tissue engineering. Recently, 3D bioprinting has emerged as a promising method for fabricating skin substitutes, offering potential applications in both drug testing and clinical treatments for severe skin injuries. This technology enables the precise deposition of cells within a biomaterial matrix to create complex tissue structures with controlled microenvironments. A major challenge in 3D bioprinted skin models is incorporating a vascular system for adequate nutrient and oxygen distribution. Here, we present a novel approach for creating a perfusable 3D vascularized skin model using two bioinks: gelatin methacryloyl (GelMA) for the dermal and epidermal layers and Pluronic F127 as a sacrificial material for vascular channel formation. This method integrates three cell types, neonatal foreskin fibroblasts, human epidermal keratinocytes, and human umbilical vein endothelial cells, to establish a biomimetic skin construct. By employing sacrificial bioprinting techniques, we successfully developed a skin model with vascularized structures that can be used for advanced in-vitro studies and regenerative therapies.